A multifactorial model of masticatory performance: the Suita study. (12th December 2015) - Kosaka, T.; Ono, T.; Kida, M.; Kikui, M.; Yamamoto, M.; Yasui, S.; Nokubi, T.; Maeda, Y.; Kokubo, Y.; Watanabe, M.; Miyamoto, Y.
Summary: Previous studies have identified various factors related to masticatory performance. This study was aimed to investigate variations and impacts of factors related to masticatory performance among different occlusal support areas in general urban population in Japan. A total of 1875 Japanese subjects (mean age: 66·7 years) were included in the Suita study. Periodontal status was evaluated using the Community Periodontal Index (CPI). The number of functional teeth and occlusal support areas (OSA) were recorded, and the latter divided into three categories of perfect, decreased and lost OSA based on the Eichner Index. Masticatory performance was determined by means of test gummy jelly. For denture wearers, masticatory performance was measured with the dentures in place. The multiple linear regression analysis showed that, when controlling for other variables, masticatory performance was significantly associated with sex, number of functional teeth, maximum bite force and periodontal status in perfect OSA. Masticatory performance was significantly associated with number of functional teeth, maximum bite force and periodontal status in decreased OSA. In lost OSA, masticatory performance was significantly associated with maximum bite force. Maximum bite force was a factor significantly influencing masticatory performance that was common to all OSA groups. After controlling for possible confounding factors, the number of functional teeth and periodontal status were common factors in the perfect and decreased OSA groups, and only sex was significant in the perfect OSA group. These findings may help in providing dietary guidance to elderly people with tooth loss or periodontal disease.